Exploring Ethics in Business Networks: Propositions for Future Research - Halinen Aino; Jokela Päivi (Palgrave Macmillan, 2022)
In this study we introduce ethics as an emerging area of business network research. Our aim is to draw researchers’ attention to ethics as a timely extension of the business network approach and to propose avenues for its future study. Business networks form a specific context for the study of ethics, yet only very little research has been conducted on the topic. Based on existing literature, we will first analyze the stands taken on defining ethics and ethical behavior in business relationships and networks. Secondly, we will address the significance of ethical behavior for business networks. To conclude, we derive four themes and a number of potential questions to be posed in future research on business network ethics. The study creates a contribution to the field of business networks by providing a state-of-the-art examination of the research topic and by laying a basis for its future study.
Extending the Business Network Approach – New Territories, New Technologies, New Terms